2020
DOI: 10.5935/1518-0557.20200003
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 improves the in vitro maturation of oocytes exposed to the intrafollicular environment of patients on fertility treatment

Abstract: Objective: To evaluate the impact of patient follicular environment with oxidative stress on oocyte quality. Methods: Patients on fertility treatment with either advanced maternal age or endometriosis were asked to donate follicular fluid collected during ovum pick-up. Follicular fluid (FF) was added (20%, 10% and 5%; %V/V) to in vitro maturation (IVM) medium with mouse oocytes. Following maturation culture, the oocytes were assessed for meios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Maside et al did not find any benefits in a porcine model [22]; however, Abdulhasan et al reported higher maturation rates and greater mitochondrial mass and function in immature bovine oocytes after 24 h in IVM medium supplemented with 40 µM of CoQ10 [23]. Moreover, immature mouse oocytes matured in vitro and co-cultured with FF from infertile women with endometriosis demonstrated a trend toward higher maturation rates after CoQ10 supplementation compared to the very low maturity reported in the control group as a result of the endometriotic environment [24].…”
Section: Coq10 Supplementation In Ivf Treatmentsmentioning
confidence: 97%
“…Maside et al did not find any benefits in a porcine model [22]; however, Abdulhasan et al reported higher maturation rates and greater mitochondrial mass and function in immature bovine oocytes after 24 h in IVM medium supplemented with 40 µM of CoQ10 [23]. Moreover, immature mouse oocytes matured in vitro and co-cultured with FF from infertile women with endometriosis demonstrated a trend toward higher maturation rates after CoQ10 supplementation compared to the very low maturity reported in the control group as a result of the endometriotic environment [24].…”
Section: Coq10 Supplementation In Ivf Treatmentsmentioning
confidence: 97%
“…The follicular environment of patients with endometriosis has a significant effect on oocyte (nuclear) development. IVM in the presence of CoQ10 appears to be a useful strategy to salvage oocytes in the follicular environment [62] . Heydarnejad et al [63] discovered that supplementing oocyte IVM medium with 30 μmol/L CoQ10 increased blastocyst formation and hatching rates; enhanced mitochondrial distribution, relative mass, and potential membrane; reduced ROS and glutathione levels; and decreased the percentage of oocytes with spindles and misaligned chromosomes.…”
Section: Coenzyme Q10 and Ivmmentioning
confidence: 99%
“…The follicular environment of patients with endometriosis severely affects the maturation of oocytes. It is emphasized that in vitro maturation in the presence of coenzyme Q10 is important for the protection of oocytes exposed to such follicular environments (83). CoQ10 supplementation during in vitro maturation is said to increase oocyte maturation rates and reduce post-meiotic aneuploidies for older women (84).…”
Section: Reproductive Endocrinologymentioning
confidence: 99%